Organic-Inorganic-Induced Polymer Intercalation into Layered Composites for Aqueous Zinc-Ion Battery - Bin, Duan; Huo, Wangchen; Yuan, Yingbo; Huang, Jianhang; Liu, Yao; Zhang, Yuxin; Dong, Fan; Wang, Yonggang; Xia, Yongyao (Chem, 2020)
Rechargeable aqueous zinc-based batteries are very attractive alternative devices for current energy storage by virtue of their low cost and high security. However, the performance of vanadium oxide cathode strongly relies on the distance of interlayer spacing. Here, we employ layered PEDOT-NH4V3O8 (PEDOT-NVO) as a cathode material, which produces an enlarged interlayer spacing of 10.8 Å (against 7.8 Å for the single NVO) by effectively conducting polymer intercalation. This cathode material exhibits an improved capacity of 356.8 mAh g−1 at 0.05 A g−1 and 163.6 mAh g−1, even at the highest current density of 10 A g−1 (with a high retention from 0.05 to 10 A g−1), and features an ultra-long lifetime of over 5,000 charge-discharge cycles with a capacity retention of 94.1%. A combination of mechanism analyses and theoretical calculations suggest that the oxygen vacancies and larger interlayer spacing through polymer assistance account for the improved electrochemical performance. [Display omitted] •A kind of organic-inorganic intercalated layered composite was synthesized•The PEDOT-NH4V3O8 has enlarged interlayer spacing and oxygen vacancies•The PEDOT-NH4V3O8 cathode exhibits excellent zinc storage performance•The mechanistic and theoretical analysis was investigated by various methods For the high demand of large-scale renewable energy storage system, zinc-ion batteries fulfill this requirement because of their abundance in Earth's total elemental reserves, higher water stability than that of alkaline (Li, Na, and K) metals, and high theoretical capacity. Here, we have developed an enlarged interlayer spacing of layered material that is capable of reversibly accommodating more Zn2+ ion while achieving high-cycle performance cathode materials for the application of zinc-ion batteries. The conducting polymer material has emerged as an important pathway for producing organic-inorganic intercalation compounds with larger interlayer spacing or oxygen vacancies, which are essential for fundamental studies as well as technique application. A kind of organic-inorganic intercalated composite can improve capacity and stability in aqueous rechargeable zinc batteries (ARZBs) as a result of the expanded interplanar spacing distance and oxygen vacancies of ammonium vanadate layered oxide.